Capital constraints and European migration to Canada: Evidence from the 1920s passenger lists - Alexander Armstrong; Frank Lewis (Queen's University, Department of Economics, 2009)
The difficulty or inability to borrow made capital market constraints an important part of the decision of potential emigrants to move from Europe to North America. We formalize the constraint with a life-cycle model, where agents jointly choose the optimal period of saving to finance migration and whether to migrate. Simulations of the model point to the potential role of preferences, the period of adjustment after arrival, and the direct migration costs in determining who will migrate and at what age; and they help account for the large wage gaps between the Old and New World. Our analysis of data from the passenger manifests of Dutch arrivals at Canadian ports from 1925 to 1927, that importantly include the saving of these immigrants, points to the promise of this approach to international migration.
Keywords: J61; N32; 330; Immigration; Canada; Wirtschaftskrise; Kapitalmangel; Verschuldungsrestriktion; Auswanderung; Europa; Kanada